Regular and Young Investigator Award Abstracts 2020
DOI: 10.1136/jitc-2020-sitc2020.0378
|View full text |Cite
|
Sign up to set email alerts
|

378 A first in-human, multicenter, open-label, dose-finding phase 1 study of the immune stimulator antibody conjugate NJH395 in patients with nonbreast HER2+ advanced malignancies

Abstract: BackgroundNJH395 is a first-in-class immune stimulator antibody conjugate (ISAC) consisting of a toll-like receptor 7 (TLR7) agonist conjugated to an anti-HER2 antibody. Antibody-mediated delivery of TLR7 may limit systemic toxicities previously seen with TLR agonists, while enhancing long-lasting antitumor immune response. In preclinical studies, NJH395 showed promising activity in HER2 expressing xenograft mouse models, and demonstrated immunogenicity and cytokine release in mice and nonhuman primates.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…This is particularly important because immune-stimulating ADCs have a very significant risk of immunogenicity through the development of anti-drug antibodies (ADA). Indeed, a recent phase I study from Novartis demonstrated that 14 out of 14 patients dosed with an immune-stimulatory ADC developed a measurable ADA response . Elimination of Fc-γ-mediated uptake into APCs is one mechanism that is being explored for attenuating ADA responses of biotherapeutics .…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly important because immune-stimulating ADCs have a very significant risk of immunogenicity through the development of anti-drug antibodies (ADA). Indeed, a recent phase I study from Novartis demonstrated that 14 out of 14 patients dosed with an immune-stimulatory ADC developed a measurable ADA response . Elimination of Fc-γ-mediated uptake into APCs is one mechanism that is being explored for attenuating ADA responses of biotherapeutics .…”
Section: Discussionmentioning
confidence: 99%
“…NJH395 is an immune-stimulator antibody conjugate consisting of a TLR-7 agonist bound to an anti-HER2 antibody. It enhances pro-inflammatory/anti-tumor responses against HER2-expressing malignant cells while limiting systemic toxicities [ 96 ]. A recent first-in-human phase I clinical trial evaluated NJH395 monotherapy in patients with non-breast HER2 + advanced malignancies ( NCT03696771 ).…”
Section: Stimulatory Pathwaysmentioning
confidence: 99%
“…A recent first-in-human phase I clinical trial evaluated NJH395 monotherapy in patients with non-breast HER2 + advanced malignancies ( NCT03696771 ). Preliminary results from the study were published in an abstract [ 96 ]. Eighteen patients were included (10 males and 8 females) with a median age of 52 years.…”
Section: Stimulatory Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations